Aminobenzofuran-containing analogues of proximicins exhibit higher antiproliferative activity against human UG-87 glioblastoma cells compared to temozolomide. Issue 12 (14th March 2023) - Shokrzadeh Madieh, Nasrin; Tanna, Sangeeta; Alqurayn, Norah Ahmed; Vaideanu, Alexandra; Schatzlein, Andreas; Brucoli, Federico
Abstract : A new series of proximicin analogues containing a benzofuran moiety as the replacement of the di-furan scaffold of the parent compound were synthesised and evaluated for their anti-proliferative activities against human glioblastoma cells U-87 MG. Abstract : A new series of proximicin analogues containing a benzofuran moiety as the replacement of the di-furan scaffold of the parent compound were synthesised and evaluated for their anti-proliferative activities against human glioblastoma cells U-87 MG. Proximicins A, B, and C are secondary metabolites produced by Verrucosispora Fiedleri MG-37, a Gram-positive actinomycete isolated from deep-sea sediment. Proximicins exhibit significant cytotoxic and apoptotic effects in a number of tumour cell lines, although further investigations on these natural products biological activity are hampered by the challenging synthesis of their constitutive di-furan unit. Therefore, the easily-synthesisable benzofuran ring was elected as a replacement of the di-furan platform, and a library of proximicin analogues was prepared in which different substituents were introduced at both the N-terminus and C-terminus of the benzofuran core unit. The novel compounds were tested against U-87 MG, as it was previously found that proximicins targeted this cancerous cell line, and the human healthy cell line WI-38. Temozolomide, the chemotherapeutic agent of choice for the treatment of glioblastoma, was used as a control. Analysis of growth inhibitory concentration values revealed that a number of furan-benzofuran-containing proximicin analogues, including 23 ( 16 ) (IC50 U-87 MG = 6.54 μg mL −1 ) exhibited higher antiproliferative activity against glioblastoma cells compared to both proximicins A–C and temozolomide (IC50 U-87 MG = 29.19 μg mL −1 ) in U-87 MG.